Synthesis and Characterization of 3,4,5-Trisubstituted Isoxazoline - V. Tekade, Pradip; Patil, K.N.; Bodkhe, P.S. (Asian Journal of Chemistry, 2016)
3-Aroyl flavanone (III) has been prepared by the condensation of dibenzoyl methane (II) with aromatic aldehyde in ethanol containing few drops of piperidine. The compound (II) on refluxing with NH2OH·HCl in DMF containing small amount of piperidine gives 4-aroyl substituted isoxazoline (IV).